PERLAWANAN MASYARAKAT IRAK TERHADAP BARAT DALAM PERSPEKTIF NOVEL ASYBĀH AL-JAHĪM (TINJAUAN STRUKTURALISME GENETIK LUCIEN GOLDMANN) - Farid, Muhammad Jillul Qur’aniyul (STIQ Amuntai, 2021)
This study aims to look at the form of Iraqi society's resistance to the West from the perspective of Yasmina Khadra's novel Asyba>h Al-Jahi>m. Asybah al-Jahim's novel is considered a form of literary reaction from the author to voice justice for the oppressed Iraqi people. This study uses a review of Lucien Goldmann's theory of genetic structuralism. There are several main ideas to find out how the approach works: human facts, collective/trans-individual subjects, and world views. The method used is dielectric. Then the material object in this study is the novel Asybah al-Jahim m which is also used as primary data. The secondary source of data is required to accommodate preliminary data. Secondary data supports data obtained from searches through books, journals, and internet media related to research. The results of this study indicate that the Iraqi people's resistance to the West in the perspective of the novel Asyba>h Al-Jahi>m is reflected through the author's world view. From this world view, it can be classified in two forms: natural resistance; both indirect matches. Keywords: Resistance, Iraq, Asyba>h Al-Jahi>m, Genetic-Structuralism.